FLOW OF QUARANTINE REQUIREMENTS AND CHARACTERIZATION OF Tilletia sp. ON WHEAT IN DETERMINING IMPORT APPROVAL - Komalasari; Maghfiroti, Ukky (AGRIBUSINESS JOURNAL, 2025)
The high volume of wheat imports in 2022, which reached 9.35 million tons, increases the risk of entry of the quarantine plant pest organism Tilletia sp., classified as Group 1 Category A1. These groups and categories cannot be treated and do not yet exist in Indonesia. Therefore, monitoring the fungus Tilletia sp. must be severe and handled appropriately. This activity aims to understand the flow of quarantine requirements and characterization of Tilletia sp. as a determinant of import approval at the Animal, Fish, and Plant Quarantine Center. The flow of quarantine requirements is implemented when the importer prepares the application file online, Phytosanitary Certificate, Invoice, Bill of Lading, Shipping Instruction, Prior Notice, Certificate of Analysis, Health Certificate, and Application for Import. Wheat commodities, if infected with Tilletia sp., will be detained, and a detention warrant will be issued; if treatment is not given, a destruction order and an extermination report will be issued. Characterization of Tilletia sp. was determined based on the frequency of washing test results. Wheat samples with Tilletia sp. >10 times must be treated with heat treatment to kill the development of spores.